Study of Moderation Verses in the Perspective of Nusantara Tafsir - Syaifuddin, Mohammad; Taufiq, Ahmad (Aqwal: Journal of Qur'an and Hadis Studies, 2023)
This study provides an understanding and interpretation of the verses of moderation in the opinion of the commentator or commentator in the archipelago. The Qur’an is not a final product, it is necessary to carry out the activities of intellectual diligence in the form of “interpretation” because the lip of the Qur’an cures me all my time to eat. Social interaction as the basic capital and characteristics of the social humanity of Muslims through understanding the verses contained in the Qur’an is a solution to  the hope of  divine pleasure and the achievement of correct understanding. The difference is the flavor of understanding, because some interpretations of  the verses of  the Qur’an  tend not to be moderate in interpretation. As a moderate Muslim discussing verses of moderation, he will generate a moderate character in personality and personality that mediates the two tensions in the epistemology of interpretation between the text and the liberal. ntolerant beliefs and attitudes in the world and views of life began to emerge at the primary and secondary levels.  The emergence of intolerance in religion as one of the factors is the lack of understanding and practice on the largest possible scale in  the  content, meaning, and context of the Qur’an itself and in matters related to the interpretation of the verses of moderation and moderation.